Pgm-Free Biomass-Derived Electrocatalysts for Oxygen Reduction in Energy Conversion Devices: Promising Materials - Zagal-Moya, J; Zagal-Moya, J; Scarpetta-Pizo, L; Scarpetta-Pizo, L (Springer, 2024)
Biomass is a low-cost, abundant and renewable resource that can be used to manufacture porous carbon-based materials for a variety of applications. Different mesoporous carbon supports can be obtained from the various synthetic approaches that are aimed at increasing the specific surface area and functionalization. Currently, most of the biomass is used for energy recovery. The circular economy approach could lead to the development of cheap and sustainable materials, and turning of wastes into a precious resource. In this review, we provide the recent advances in the field of electrochemistry for porous carbon materials derived from biomass, which offers wider applications in proton exchange membrane fuel cells (PEMFCs), anion exchange membrane fuel cells (AEMFCs) and Zn-air batteries (ZABs). The focus is on understanding the required properties of the materials and the role of synthetic pathways in platinum group metal (PGM) free electrocatalysts. The most promising materials are evaluated towards the oxygen reduction reaction (ORR) in PEMFC, AEMFC, and ZAB. The results achieved showed that the expected performances on these energy conversion devices still lack for deployment in practice, especially if compared with commercially available PGM-free electrocatalysts. This review article provides insights on how to improve the actual electrocatalytic activity of biomass-derived materials. Graphical Abstract: [Figure not available: see fulltext.] © 2023, The Author(s).